Barbarian's prize - Dixon, Ruby, 1976- (Dixon, Ruby, 1976- Ice planet barbarians series, 2023)
"Tiffany doesn't care about all the attention she's getting from the alien men, but there is one particular hunter she can see herself with--if only she can find a way to move forward from the past... It's hard being the most popular girl on the ice planet. The alien men are falling all over themselves to impress me in the hopes that I'll take them to my furs. But they don't know my secrets. And they don't realize that behind my smile, I just wish they'd take their courting presents and their competitions for my affection and go away. I want to be left alone. But on a planet where women are a scarcity, that won't be happening. If I had to choose a mate... it'd be someone with a gorgeous blue body, big horns, and the most intense gaze ever. Someone who knows the truth of what happened to me and why I don't like attention. Patient, handsome Salukh knows my secrets. He knows why I have nightmares and why I don't trust anyone. He's willing to let me "experiment" with him. I can use him. Take what I need from him to work through my trauma. He's been a good friend and the best shoulder to cry on. There's one small problem. When it comes to us, he doesn't just want to be my friend. He wants to be my forever. And day by day, he's getting harder to resist..."--